Factors That Play Roles in COVID-19 Transmission Among Healthworkers - Hartati B Bangsa; Ray Wagiu Basrowi (The Indonesian Journal of Community and Occupational Medicine, 2022)
Introduction: The impact of COVID-19 has spread around the globe since first announced in March 2020 by WHO and was first acknowledged in an occupational setting, and up to now, becoming the major percentage of the cases. 1. Regardless of the prompt response made, COVID-19 infection cases among healthcare workers have risen quickly and high. It is essential to understand the features that play roles in COVID-19 transmission among healthcare workers in occupational settings to build a better understanding in minimizing the occupational hazards and prevent such cases.Methods: This literature review was conducted in April 2022. Research related to the COVID-19 infection among healthcare workers in an occupational setting by using specific keywords including COVID-19, healthcare workers, occupational on two database Pubmed and Google Scholar.Results: 12 articles were analysed for the literature review. Recognizing hazardous work characteristics and demographic characteristics as the risk of transmission among healthcare workers can help optimizing the protection and reduce transmission cases among healthcare workers in an occupational setting.Conclusions: Having a better understanding of factors that play a role in COVID-19 transmission among healthcare workers in the occupational setting is essential to create a better policy implemented to safeguard healthcare workers’ health and safety. The provision of health services to patients relies on professional staff who feel safe and well protected. Therefore, ensuring workers’ safety and health is critical to keep transmission rates low. COVID-19 is a trigger for the world of health, especially occupational health in socialization and commitment to the implementation of the control hierarchy and also certainty in making policies.